Cu/Cu direct bonding by metal salt generation bonding technique with organic acid and persistence of reformed layer. (19th January 2015) - Koyama, Shinji; Hagiwara, Naoki; Shohji, Ikuo
Abstract: In this study, the effect of the metal salt generation bonding technique on the strength of a direct-bonded copper–copper interface was investigated. Copper surfaces were modified by boiling in several types of organic acids, and direct bonding was performed at a bonding temperature of 423–673 K under a load of 588 N (for a bonding time of 0.9 ks). As a result of the surface modification, bonded joints were obtained at bonding temperatures of 150 K (after treatment with formic acid) and 100 K (after citric acid treatment) lower than that required for the unmodified surfaces. In addition, the duration of the modification effects was investigated by exposing the modified surface to an air atmosphere furnace kept at 323 K. The bonding strength of the citric acid-modified surface remained unchanged even after 168 h, whereas that of the surface modified with formic acid decreased within 6 h.